1979
DOI: 10.1007/bf01041269
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical localization of glycosidases in dog epididymis

Abstract: The histochemical localization of five glycosidases was studied in the epididymis of mature dogs. beta-Galactosidase showed a distinct to strong reaction in the epithelium of the ductuli efferentes and throughout the whole length of the ductus epididymidis. beta-N-Acetylglucosaminidase reactivity was weak in the initial segment, but increased significantly in the middle and terminal segment. The maximum beta-glucuronidase activity was found in the ductuli efferentes and in the initial segment. The alpha-mannos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…localized {3-glucuronidase in the early stages of spermatogenesis in rat. This observation is in sharp contrast to the localization of hyaluronidase which is uniformly concentrated in various stages of germ cell line 18 and specifically at the junctions of cells.te As compared to the localization in human epididymis, Sinowats et al 19 epididymis in dog, whereas Hayashi/" noted positive granules of f)-glucuronidase situated supranuclearly in some cells in the cauda region. The difference in the staining pattern in caput and cauda epididymis of humans is evident, which may represent some modifications of the enzyme.…”
Section: Discessionmentioning
confidence: 66%
“…localized {3-glucuronidase in the early stages of spermatogenesis in rat. This observation is in sharp contrast to the localization of hyaluronidase which is uniformly concentrated in various stages of germ cell line 18 and specifically at the junctions of cells.te As compared to the localization in human epididymis, Sinowats et al 19 epididymis in dog, whereas Hayashi/" noted positive granules of f)-glucuronidase situated supranuclearly in some cells in the cauda region. The difference in the staining pattern in caput and cauda epididymis of humans is evident, which may represent some modifications of the enzyme.…”
Section: Discessionmentioning
confidence: 66%
“…It is possible that both populations of acid hydrolasebearing particles come from the epithelium of the duct since it has been demonstrated by other authors that the histochemical activity of AP, NAG, and GLU is almost entirely confined in the epithelial cells (Sinowatz et al, 1979;Moniem and Glover, 1972). Moreover, Kemp and Killian (1978) found that the epithelial cells of the rat epididymis separated at l g in albumin gradients contained most of the activity of various acid glycosidases.…”
Section: Discussionmentioning
confidence: 94%
“…The GPs coating the surface of boar epididymal sperm are gradually lost due to the hydrolytic effects of enzymes secreted by the epididymal epithelium [6]. Canine epididymal fluid contains various types of glycosidases, e.g., N-acetyl-β-glucosaminidase, β-galactosidase and α-manosidase [26]. Thus, DBA-and SBA-lectin-binding GPs on canine sperm surface are therefore presumably removed by the effects of the enzymes in the epididymal fluid during sperm transport through the cor- pus epididymides and the cauda epididymides.…”
Section: Discussionmentioning
confidence: 99%